NOVEL ROLES FOR NEU1 SIALIDASE IN LIPOPROTEIN METABOLISM AND INFLAMMATION: BRIDGING MOLECULAR MECHANISMS IN ATHEROSCLEROSIS - Gyulay, Gabriel (My University, 2014)
Atherosclerosis is a complex multi-factorial disease that involves the interaction of many cell types and a plethora of molecular events. Initiation of the disease occurs when circulating LDL gets trapped in the sub-endothelial space of arteries, where LDL is oxidized causing inflammatory responses by endothelial cells. This results in recruitment and differentiation of monocytes into macrophages; macrophages in turn continue to take up cholesterol and propagate inflammation. Such a gloomy milieu of immune cells, lipids, and smooth muscle cells can give rise to atherosclerotic plaques, which then cause stenosis, vascular stiffening and eventually thrombosis. Common risk factors such as cholesterol levels, lifestyle and genetic predisposition can accelerate this potentially life threatening series of events. The downstream long-term effects of atherosclerosis, including heart disease and strokes, are now the number one cause of death in the world. While a large amount of knowledge and evidence is available in understanding this disease, prevention and treatment strategies remain somewhat ineffective. Sialylation of immune cells, lipoproteins and cellular receptors has been previously implicated in metabolic and molecular pathways relevant to atherosclerosis; however, little is known about the functional role of sialidase in these processes. Sialidase cleaves sialic acid, and is a ubiquitously expressed and evolutionarily conserved protein with essential functions in many life forms. In this study, we sought to investigate the impact of sialidase activity on atherosclerosis, emphasizing the interaction of lipid metabolism and inflammation. We have demonstrated a significant role for sialidase in cholesterol iv and lipoprotein metabolism in vivo. Specifically, hypomorphic sialidase mice have increased hepatic storage of lipids and triglycerides, decreased VLDL production, lower circulating LDL levels and alterations in regulation of LDLR. Mice over-expressing hepatic human sialidase have increased atherosclerotic lesion formation, higher serum cholesterol esters and lower levels of hepatic LDLR and SRB-1 protein. In vitro, we have shown that VLDL can induce differentiation and cytokine production in monocytes coupled with an up-regulation of Neu1. Inhibition of sialidase using DANA attenuated VLDL-induced monocyte differentiation and lipid uptake, as well as activation of macrophages, implicating Neu1 in inflammatory processes associated with initiation of atherosclerosis. Furthermore, we have shown that hypomorphic sialidase activity increases LDLR-dependent LDL uptake and cholesterol efflux to HDL in macrophages. We conclude that reduction of sialidase activity can lead to an atheroprotective phenotype with multiple effects on mechanisms involved in disease progression. This work represents novel contributions into delineating both metabolic and inflammatory processes of atherosclerosis and enables the advancement of future treatment strategies.
Keywords: Atherosclerosis; Sialidase; Neuraminidase; Neu1; Lipoprotein; Inflammation; Molecular Biology; Molecular Biology